36. Monitoring motor evoked potentials of vagus nerve with endotracheal tube electrodes in brainstem surgery. Issue 12 (December 2016) - Prandi, P.; Tondo, G.; Panzarasa, G.; Cantello, R.
Abstract : In surgery around brainstem for preservation of swallowing function, monitoring of the corticobulbar tract of the X cranial nerve – and not only vagal rootlets – is needed. A few researchers have studied intraoperative monitoring of the vagus nerve corticobulbar pathway. In the past, X nerve has been monitored using needle or hook-wire electrodes, endoscopically or laryngoscopically placed in the vocal fold. Because of their complexity and invasiveness, these techniques have not been widely used. New studies with vagal MEPs have been recently published, although they required needle insertion into the vocal cord. Reports with non-invasive methods are still lacking. In this work we report our series of vagal nerve motor evoked potentials using endotracheal adhesive electrode in surgery around brainstem. In 26 patients who have undergone surgery around brainstem vocal cord MEPs were recordable in about 70% of cases. Correct electrode placement is the main issue to obtain signals. Latencies varied from 14 to 20 msec and amplitude from 40 to 200 uv. In 3 cases there was MEP loss and the patients suffered of post operative dysphagia. MEP recorded with endotracheal tube adhesive electrodes is a safe, effective and reliable method to monitor corticobulbar vagal tract.